Pengaruh Disiplin, Pengembangan Karir Dan Motivasi Terhadap Kinerja Karyawan Padan PT SatNusa Persada Tbk - Safitriani Safitriani; Hendri Herman (Jurnal Abdi Ilmu, 2020)
At present, employee management is very important for the company. Therefore, companies should be able to educate their workers, such as doing good discipline, developing employee careers, and providing motivation to employees, so that the creation of good performance for the company. The purpose of this research is to test and analyse the influence of discipline, career development and motivation towards employee performance. This research was conducted at PT SatNusa Persada TBK in Batam. Samples taken with non probability sampling techniques by purposive sampling method, and data collection techniques using survey method through questionnaires. The size of the samples taken using the Slovin formula is 152 respondents. Data processing methods use multiple linear regression methods with SPSS aids (Statistical Product and Service Solution) version 25. The calculation result of the coefficient of determination (R2) obtained by 0.906 or 90.6% of employee performance variables (Y) can be explained by disciplinary variables, career development and motivation while the remaining 9.4% is influenced by other factors not included in this study. Based on the results of the test, it is known that discipline, career development and motivation are influential and significant to the employee's performance.